The Effectiveness of Interactive Learning Media Based on Edutainment in Writing Skills for Text Procedure - ., Kustyarini; Utami, Sri; Koesmijati, Endang (KnE Social Sciences, 2020)
Writing text procedures is one form of text type found in Indonesian language learning that applies the 2013 Curriculum. In this study, researchers focused on writing text procedure skills using edutainment-based learning media. The challenge is implementing a learning system that involves the senses simultaneously. Using a text-based approach, the 2013 Curriculum Indonesian Language Learning trains individuals to solve problems and think critically in accordance with real life. The text that describes a step or way of dealing with it is a text procedure. The main purpose is to make it easier for readers to understand things quickly and precisely. The main objective in this study is to see whether the creation of a happy atmosphere, via the use of edutainment media, will affect the processing, storing and receiving information, and feedback for learning text procedures. The learning outcomes after the use of edutainment-based interactive media procedure for writing text skills increased in comparison to the scores before the use of the media. Therefore, this learning medium is very effective in increasing individual motivation and learning outcomes writing and developing creative ideas. Keywords: efficacy, interactive learning media, edutainment, procedural text, writing skills